Use of peninsula valdes (Patagonia Argentina) by migrating red knots (Calidris canutus rufa) - Musmeci, Luciana Raquel (2012)
Red Knots (Calidris canutus rufa) that winter in southern South America stop on Peninsula Valdes, Patagonian Argentina, on their northern passage. The Peninsula comprises two large gulfs, each of which has two high and two low tides per day; high tides in San José Gulf correspond to low tides in Nuevo Gulf and vice versa. We conducted weekly censuses of Red Knots on several beaches on these gulfs between March and May in 2006 and 2007 and observed marked individuals. We undertook an aerial survey of the coasts of the two gulfs each April. The use of the different beaches on the two gulfs by Red Knots varied significantly in both years of the study, and the patterns of use differed between 2006 and 2007. In both years, maximum numbers of Red Knots were counted in April. Observations of marked individuals confirmed that Red Knots use more than one beach on Peninsula Valdes, and on one occasion marked individuals were seen on the same day using beaches on both gulfs, thereby maximising their foraging time. Our observations suggest that Peninsula Valdes is an important place on the northern migration route of Red Knots. © BirdLife Australia 2012.